Tailoring nanostructured, graded, and particle-reinforced Al laminates by accumulative roll bonding - Göken, Mathias; Höppel, Heinz Werner (Advanced Materials, 2011)
Accumulative roll bonding (ARB) is a very attractive process for processing large sheets to achieve ultrafine-grained microstructure and high strength. Commercial purity Al and many Al alloys from the 5xxx and the precipitation strengthened 6xxx alloy series have been successfully processed by the ARB process into an ultrafine-grained state and superior ductility have been achieved for some materials like technical purity Al. It has also been shown that the ARB process can be successfully used to produce multi-component materials with tailored properties by reinforcement or grading, respectively. This allows optimizing the properties based on two or more materials/alloys. For example, to achieve high corrosion resistance and good visual surface properties it is interesting to produce a composite of two different Al alloys, where for example a high strength alloy of the 5xxx series is used as the core material and a 6xxx series alloy as the clad material. It has been shown that such a composite achieves more or less the same strength as the core material although 50% of the composite consists of the significant softer clad alloy. Furthermore, it has been found, that the serrated yielding which typically appears in 5xxx series alloys and limits applications as outer skin materials completely disappears. Moreover, the ARB process allows many other attractive ways to design new composites and graded material structures with unique properties by the introduction of particles, fibres and sheets. Strengthening with nanoparticles for example is a very attractive way to improve the properties and accelerate the grain refining used in the severe plastic deformation process. With an addition of only 0.1 vol.-% Al_2O_3 nanoparticles a significantly accelerated grain refinement has been found which reduces the number of ARB passes necessary to achieve the maximum in strength. The paper provides a short review on recent developments in the field of ARB processing for producing multicomponent ultrafine-grained sheet materials with tailored properties.
WW1::905